Nasal Dermoplasty for Recurrent Polyps in a Patient with Churg-Strauss Syndrome - George Anastasopoulos; Theophanis Machas; Sofia Kegioglou; Demetra Rapti (Case Reports in Otolaryngology)
Nasal dermoplasty for recurrent polyps (NDRP) is a new technique for the surgical treatment of this condition. Churg-Strauss syndrome is characterized by the presence of nasal polyps with a great tendency for relapse after surgical or pharmaceutical treatment. It is the first time that we use NDRP to treat nasal polyps in a patient with Churg-Strauss syndrome. The patient was a 33-year-old female suffering from Churg-Strauss syndrome having had multiple operations in the past for recurrent polyps. NDRP was performed on the left nostril only. The mucosa of the left nasal vault was replaced by a split-thickness skin graft (modified dermoplasty). On the right nostril, polyps were removed and the ostia of the paranasal sinuses were enlarged as in typical endoscopic sinus surgery. The skin graft had a successful take and eight months after the operation no polyps are detected on the left side while polyps have recurred on the right nasal cavity. Applying the technique to a single nostril has several advantages, namely, the reduction of the operational time and therefore the risks for the patient from a prolonged general anaesthetic and the ability to judge the efficacy of the technique on the same patient.